Sistem Deteksi Kecanduan Pornografi Berbasis Chatbot Menggunakan Pornography Addiction Screening Tool (PAST) - Muhammad, Raditya; Ardimansyah, Mochamad Iqbal (Building of Informatics, Technology and Science (BITS), 2022)
The use of the internet not only brings benefits but also harms the ease of access to pornographic content. Pornographic content is not solely available on adult websites but is also spread on social media accessed by many children to adults. As a result, problems arise due to pornography addiction, such as rape, sexual orientation deviation, and sexual crimes against children. Uniquely, pornography addiction is hard to detect objectively compared to drug or alcohol addiction. This study aims to develop a pornography addiction detection system in the form of a chatbot-based mobile application. The choice of chatbot is because this system supports interactive automatic communication patterns and guarantees the privacy of its users. This study adopts a psychological measurement technique Pornography Addiction Screening Tool (PAST), as a benchmark in developing application logic. Meanwhile, chatbot application development uses the waterfall method which has been tested by best practices as a software development method. Tests performed are in a developer environment. The system validation mechanism uses the Black-box testing method to observe the execution of the application when it runs the functionality that was designed beforehand. In addition, the usability measurement level application is adopted from the System Usability Scale (SUS) method. From the test results, it was found that the pornography addiction detection system operates normally and can be used as a supporting medium for handling pornography addiction by psychiatrists.